A Scoping Review: Factors Associated with Pruritus in CKD (Chronic Kidney Disease) Patients Undergoing Dialysis - Tahratul Yovalwan; Fitri Arofiati (Universitas Aisyah Pringsewu, 2023)
Chronic Kidney Disease (CKD) is characterized by progressive loss of kidney function over time due to kidney damage or reduced glomerular filtration rate (GFR) of less than 60 mL/min/173m2 for more than 3 months. The increased levels of urea in patients with chronic kidney failure can cause pruritus known as uremic pruritus or chronic kidney disease-associated pruritus (CKD-ap). The research method that will be used is PRISMA. These scoping reviews will use a systematic approach and selection process. Library sources were traced from the Proquest, PubMed, Scopus and Google Scholar databases. This scoping review aims to examine the associated factors with pruritus in patients undergoing dialysis. Factors related to uremic pruritus, namely based on analysis through scoping reviews that have been carried out on 8 articles, it was found that the most widely used study design was cross-sectional, the most widely used type of dealisis is hemodialysis with the number of articles is 3 articles and the number of patients that is male 505 samples (60.4%) and women 331 samples (39.6%) with the Total is 836 samples. Factors associated with uremic pruritus are gender, age, the dose of dialysis, duration of dialysis, urea/urea, C-Reactive Protein (CRP), and parathyroid hormone (PTH).The conclusion is that the factor that most dominant factor affecting pruritus is the factor of laboratory results, which is a factor that can be modified. Abstrak: Chronic Kidney Disease (CKD) ditandai dengan hilangnya fungsi ginjal secara bertahap dari waktu ke waktu karena kerusakan ginjal atau ketika laju filtrasi glomerulus (LFG) kurang dari 60mL/menit/1,73 m2 selama lebih dari 3 bulan. Peningkatan kadar ureum pada penderita gagal ginjal kronik dapat menyebabkan pruritus yang dikenal dengan istilah pruritus uremik atau chronic kidney disease associated pruritus (CKD-ap). Metode penelitian menggunakan PRISMA. Scoping review ini menggunakan pendekatan dan proses seleksi yang sistematis. Sumber pustaka ditelusur dari database Proquest, PubMed, Scopus dan Google Schoolar. Scoping review ini bertujuan untuk menelaah faktor-faktor yang berhubungan dengan pruritus uremik pada pasien yang menjalani dialisis. Faktor yang berhubungan pruritus uremik yaitu berdasarkan analisis melalui scoping review yang telah dilakukan pada 8 artikel maka didapatkan hasil bahwa desain penelitian paling banyak digunakan yaitu cross sectional, tipe dealisis paling banyak digunakan yaitu hemodialisis dengan jumlah artikel yaitu 3 artikel dan jumlah pasien yaitu Laki-laki 505 sampel (60,4%) dan perempuan 331 sampel (39,6%) Total 836 sampel. Faktor yang berhubungan dengan pruritus uremik adalah jenis kelamin, umur, dosis dialisis, lama dialisis, urea/ureum, C-Reactive Protein (CRP), dan hormon paratiroid (PTH). kesimpulan yang paling dominan mempengaruhi pruritus adalah faktor hasil laboratorium yaitu faktor yang mampu untuk dimodifikasi.